MARKERS IN TIV NEGATION SYNTAX - Agum, Mimi Sarah; Ishima, Justus Leo Jighjigh (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
The syntax of negation in Tiv, a noteworthy Benue-Congo language spoken in Nigeria, presents an interesting paradigmatic structure, characterized by notable complexities and asymmetries. Leveraging Chomsky's influential Principles and Parameters approach, this study examines the language's negation system, employing descriptive and qualitative methods to elicit and analyze the data. The findings reveal a significant interplay of pre-verbal and post-verbal negation, as Tiv's negative markers "ei", "de", and "ga" exhibit a thoughtful pattern of negation, differing from conventional expectations and highlighting the language's distinctive characteristics. This configuration is marked by the deliberate use of "ei" and "de" in imperative negation in sentence-initial positions, while "ga" effectively negates declarative statements in sentence-final positions, demonstrating a clear relationship between syntax and semantics. Ultimately, Tiv's deviation from the linguistic norm underscores its unique approach to negation, where sentence type and communicative intent guide the placement of negative markers, revealing the language's complex and effective negation system.